2011
DOI: 10.1021/jf104561h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antrodia camphorata on Alcohol Clearance and Antifibrosis in Livers of Rats Continuously Fed Alcohol

Abstract: Alcoholic fatty liver disease (AFLD) is the result of an excessive or chronic consumption of alcohol. Nine male Wistar rats per group were randomly assigned to one of the following drinking treatments: a 20% (w/w) alcohol solution (ALC); a 20% (w/w) alcohol solution cotreated with 0.25 g silymarin/kg BW/day; or a 20% (w/w) alcohol solution cotreated with 0.025 g Niuchangchih ( Antrodia camphorata )/kg BW/day for 4 weeks. Rats with cotreatments of silymarin or Niuchangchih had smaller (p < 0.05) relative liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Chronic alcoholic hepatitis in rats was induced as described elsewhere. 20 Since our previous study indicated that a dosage of 1 g taurine/kg BW and 0.25 g silymarin/kg BW accelerated alcohol clearance in a rat model of chronic alcohol consumption, 20 the rats in the current study were randomly divided into four treatment groups with eight rats each: (1) water per day (p.o. ); and (4) 1X silymarin group (Sil): 3 g alcohol/kg BW + 0.25 g silymarin/kg BW/day in 3 mL of sterile distilled water per day (p.o.).…”
Section: Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic alcoholic hepatitis in rats was induced as described elsewhere. 20 Since our previous study indicated that a dosage of 1 g taurine/kg BW and 0.25 g silymarin/kg BW accelerated alcohol clearance in a rat model of chronic alcohol consumption, 20 the rats in the current study were randomly divided into four treatment groups with eight rats each: (1) water per day (p.o. ); and (4) 1X silymarin group (Sil): 3 g alcohol/kg BW + 0.25 g silymarin/kg BW/day in 3 mL of sterile distilled water per day (p.o.).…”
Section: Dietmentioning
confidence: 99%
“…19 Our recent study indicated that taurine downregulates lipogenesis, oxidative stress, and inflammatory cytokines in a rat model of chronic alcohol consumption. 20 However, the precise signaling involved in the beneficial effect of taurine on alcohol-induced liver injury is still obscure. Therefore, this study investigated the precise signaling conferred by taurine in alcohol-induced liver injury.…”
Section: Introduction Ementioning
confidence: 99%
“…MMP-2, -8, -9, and -13 cause fibrinolysis and tissue remodeling, which results in the progression of liver fibrosis (Consolo et al, 2009). It was reported that higher hepatic MMP-2/-9 activities are observed in rodents treated with carbon tetrachloride (Shyu, Kao, & Yen, 2008), high-fat/cholesterol diet , and chronic alcohol consumption (Wu et al, 2011). Hsu et al (2010) reported that a high-cholesterol diet increases hepatic stress-related molecules, i.e.…”
Section: Antioxidant Status and Liver Damagementioning
confidence: 99%
“…Hence, quicker alcohol metabolism in hepatocytes results in less damage (Wu et al, 2011). The previous researches related to the alcohol metabolism of Tau against chronic alcohol consumption seem insufficient.…”
Section: Introductionmentioning
confidence: 99%